2001
DOI: 10.2460/ajvr.2001.62.252
|View full text |Cite
|
Sign up to set email alerts
|

Experimental infection of European wild boars and domestic pigs with pseudorabies viruses with differing virulence

Abstract: European wild boars are susceptible to transmission of PrV infection from domestic pigs and vice-versa. The PrV isolate BFW1 is of low virulence and seems to be adapted to the wild boar population from which it was isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 21 publications
(35 reference statements)
2
43
0
Order By: Relevance
“…Studies carried out with the use of PrV isolates from the US and East Germany produced mild clinical symptoms in experimentally infected wild boars and domestic pigs Mü ller et al 2001). Furthermore, field observations suggest that PrV infection in free-living wild swine may produce only mild respiratory symptoms and may go unnoticed (Mü ller et al 2000), supporting the hypothesis that PrV strains in wild boars may be less virulent than those of domestic pigs Mü ller et al 2001;Schulze et al 2010). Indeed, only occasional clinical cases were reported from an outbreak of PrV infection in wild boars in south-central Spain (Gortazar et al 2002) and two cases from an endemically infected area in East Germany (Schulze et al 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies carried out with the use of PrV isolates from the US and East Germany produced mild clinical symptoms in experimentally infected wild boars and domestic pigs Mü ller et al 2001). Furthermore, field observations suggest that PrV infection in free-living wild swine may produce only mild respiratory symptoms and may go unnoticed (Mü ller et al 2000), supporting the hypothesis that PrV strains in wild boars may be less virulent than those of domestic pigs Mü ller et al 2001;Schulze et al 2010). Indeed, only occasional clinical cases were reported from an outbreak of PrV infection in wild boars in south-central Spain (Gortazar et al 2002) and two cases from an endemically infected area in East Germany (Schulze et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Prior experimental and field studies demonstrated that some of the subjects were PrV PCR positive, but antibody negative (Mü ller et al 2001;Ruiz-Fons et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The disease occurs worldwide and causes big economic losses due to its direct effect on domestic pigs and to its indirect impact on the international trade of pigs and their products (Moynagh 1997). Many European countries have become ADV free (Moynagh 1997;Müller et al 2001) due to the implementation of control and eradication programs in their domestic pigs (e.g. The Netherlands, Denmark, or Germany).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst CSF virus, for example, is supposed to spread rapidly when introduced among susceptible wild boar (Artois et al, 2002), the observed low-speed spread of ADV in wild boar might be a result of the different nature and pathogenesis of this virus on the one hand and geographical features on the other hand. In contrast to highly contagious CSF virus (Artois et al, 2002), ADV variants circulating in wild boar seem to be perfectly host adapted (Pannwitz et al, 2012), resulting in more latent or subclinical infections with reduced virus excretion due to very low virulence (Müller et al, 2001(Müller et al, , 2011. Only spontaneous reactivation results in the formation of infectious virions, which are shed and may infect adjacent susceptible animals (Mettenleiter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%